A Conceptual Study on Factors Influencing Green Banking Facilities in India - Dr. S. Selvaraj (Journal of Corporate Finance Management and Banking System, 2023)
Green banking is a relatively new concept in comparison. It is a paperless banking system that saves on operating expenses and is good for the environment. Green Banks are organisations with a single goal: to speed up the transition to sustainable energy and stop climate change. This conceptual study was carried out to investigate several aspects of the performance of green banking. To learn more about the green banking performance and policies, several previously published papers were examined. These studies cover a variety of subjects, such as Determinants of Green Banking Adoption in Emerging Economies, Determinants of Green Banking Implementation, Determinants of Green Banking Expectations among Customers, and Determinants of Customers' Expectations Toward Green Banking Practices in India.